A COMPARATIVE ANALYSIS OF E-ADVERTISEMENT BETWEEN JD.ID AND SHOPEE CUSTOMERS IN MANADO - Adoeng, Wulandari; Kalangi, Josep B.; Wangke, Shinta J. C. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2019)
Abstract: Online advertisement business used electronic commerce tools to build marketing strategy, theories on advertisement and customer purchase behavior because of potential market segmentation. Likewise, online advertisement include contextual ads on examine banner ads, rich media ads, social network advertising, online classified advertising, and marketingÂ  email like spam according to Goldfarb and Tucker (2011). The increasing of online shop based on website and mobile apps in Indonesia make companies must have something different and relevant topics in promoting their products and services in order to get more sales. This research want to find out is there any difference between JD.ID and Shopee e-Avertisement based on information quality, brand recognition, willingness to purchase, price, and color. This research uses quantitative method. Questionnaire is used to collect the data, the sample is 100 respondents of JD.ID and Shopee customers in Manado. This research derived and examined by using Independent Sample t-Test. This research finding that there are differences between JD.ID and Shopee e-Advertisement based on the effectiveness of social media, content, information quality, brand recognition, willingness to purchase, price, and color. From the results, it is recommened for this 2 big e-commerce to develope and keep up their advertisement to interest customers.Keywords: e-advertisement, information quality, brand recogniton, willingness to purchase, price, color.